Service-ability : create a customer centric culture and achieve competitive advantage - Robson, Kevin (Wiley, 2013)
Times have changed. Long gone are our days of being kings of the manufacturing industry, we are now immersed in the world of 'service' where the relationship between an organization and the customer is an integral part of the 'product' offering. The nation is suffering from a widespread lack of truly customer-satisfying service. We lack the very thing that we need to make this new paradigm work efficiently: service-ability. Organizations of all kinds are facing high customer churn, serious customer antagonism, loss of consumer confidence and plummeting customer satisfaction. Res.